The P-T-t path of pelitic gneisses in the Zanhuang Complex: Further constraints on the Palaeoproterozoic tectonic evolution of the Trans-North China Orogen, North China Craton. (1st May 2021) - Zou, Lei; Guo, Jing-Hui; Yang, Chong-Hui; Du, Li-Lin; Liu, Ping-Hua
Graphical abstract: Highlights: Inclusion-type staurolite further defines the prograde metamorphic stage and P-T conditions. U–Pb age data reveal that timing of peak metamorphism is approximately 1839–1831 Ma. A clockwise P–T–t path has been reconstructed, indicating a continuous continental collision and tectonic uplift process. Abstract: The Zanhuang Complex, situated on the eastern margin of the central section of the Trans-North China Orogen (TNCO), North China Craton, mainly comprises Archean-Palaeoproterozoic tonalite-trondhjemite-granodiorite (TTG) gneisses, migmatites, granites, metavolcanic rocks, and metasedimentary rocks. Petrographic observations of garnet-bearing pelitic gneisses from the south-eastern Zanhuang Complex show three distinct mineral assemblages (M1 -M3 ) that correspond to three different metamorphic stages. The interpreted prograde metamorphic stage (M1 ) is mainly represented by the cores of garnet porphyroblasts with fine-grained inclusions of biotite + plagioclase + staurolite + kyanite + quartz + ilmenite. The peak metamorphic stage (M2 ) is mainly represented by garnet mantles and a matrix-type mineral assemblage of kyanite + biotite + plagioclase + quartz + ilmenite + melt. The retrograde metamorphic stage (M3 ) is represented by the presence of sillimanite with garnet rims + biotite + plagioclase + quartz + ilmenite + magnetite. Quantitative phase equilibria modelling constrains the pressure–temperature ( P–T ) conditions of the M1 and M2 stages to 640–670 °C/7.3–7.5 kbar and 705–760 °C/7.9–9.1 kbar, respectively. The zircons and monazites in the Zanhuang pelitic gneisses all record consistent ages of 1839–1831 Ma, which most likely represent the near-peak metamorphic age. Thus, a clockwise P-T- time ( P-T-t ) path is determined for the garnet-bearing pelitic gneisses from the Zanhuang Complex. The petrological and geochronological evidence from the pelitic gneisses in the Zanhuang Complex in this paper suggests that the TNCO might have experienced continuous continental collision and rapid tectonic uplift at ca. 1839–1831 Ma, thereby providing a metamorphic constraint on the Palaeoproterozoic tectonic evolution of the TNCO.